Method Of Implementation and Quality Control Of Shearwall In Podomoro Golf View Apartment Project - Hutama, Vigie Priantika Putra (Equivalent: Jurnal Ilmiah Sosial Teknik, 2024)
Shearwalls are an important structural element used in high-rise buildings to withstand lateral forces due to earthquakes, serving as a building reinforcement and stabilizer. This study aims to understand the stages of shear wall implementation and quality control processes in the field, especially in the Podomoro Golf View Apartment project on Dahoma Tower, 15th floor, zone D4, with SW3 shear wall type. Data is collected through field reviews, interviews, and documentation, as well as additional data from the project. The results of the study show that the implementation of SW3 shear wall is in accordance with the schedule and standards, using BJTD 40 threaded steel that has been tensile tested according to the requirements. The casting and dismantling method of formwork speeds up the binding time of concrete. Although some defects were found on the side of the shear wall, repairs were made immediately, and concrete treatment was carried out to ensure quality. The quality of concrete on the shear wall reaches Fc 30 with a slump test value of 12 ± 2 cm, in accordance with the provisions of PBI 1971. The entire construction project of Podomoro Golf View Apartment is going according to the plan and requirements, although there are some minor issues that can be tolerated and overcome.